Relationship Between Self-Efficacy, Functional Capacity, Fatigue, and Quality of Life Among Patients with Congestive Heart Failure - Zul Ashfi; Kgs. M. Faizal; Rezka Nurvinanda (Inspirasi Foundation, 2027)
Introduction : Congestive Heart Failure (CHF) is a chronic medical condition in which the heart is unable to pump blood effectively to meet the metabolic needs of the body's tissues. When the heart's pumping function is impaired, blood can back up (congestion) in the lungs, liver, abdomen, or lower extremities, causing fluid buildup (edema) in these tissues. Objective: Congestive Heart Failure (CHF) is a chronic medical condition in which the heart is unable to pump blood effectively to meet the metabolic needs of the body's tissues. When the heart's pumping function is impaired, blood can back up (congestion) in the lungs, liver, abdomen, or lower extremities, causing fluid buildup (edema) in these tissues Method: The type of research used is quantitative with the research design used being descriptive analytical through an approach. Cross Sectional namely conducting a cross tab between the dependent variable and the independent variable. The sample in this study was 92 CHF patients. Data analysis using the test pesonality with a confidence level of 95%. Result: The results of the study were to find out between the dependent variable, namely the quality of life in CHF patients and the independent variables consisting of self efficacy, six minute walk test And fatigue. The results of the statistical test of the self efficacy variable obtained a p value of 0.019, the variable six minute walk test obtained a p value of 0.009 and the variable fatigue obtained a p value of 0.000 Conclusion: It is recommended that patients with congestive heart failure (CHF) improve compliance with pharmacological and non-pharmacological therapy through ongoing education, healthy lifestyle changes, and active family involvement in the care process to prevent relapse and improve quality of life